Infrastructure investment, private finance, and institutional investors: Asia from a global perspective - Georg Inderst (Asian Development Bank Institute (ADBI), 2016)
This study evaluates infrastructure investment and finance in Asia from a global perspective. It provides an overview on infrastructure needs and the various sources of private finance, globally and within Asia, and creates a "bigger picture" for the demand and supply of capital for infrastructure by using a simple framework, i.e., percentages of gross domestic product. The picture is expectedly not uniform across Asia, but some interesting features emerge from global comparisons. Overall, the private sector still plays a relatively subdued role. Bank loans dominate private infrastructure finance, and there is much scope for the further development of capital markets. The volumes of listed and unlisted investment instruments, of project finance and of public-private partnerships, are still small in relation to investment needs and well below the global average. However, there are some notable exceptions. Institutional investors are widely seen as a new financing source for infrastructure. There are some distinctive features in Asia, such as the prominence of large pension reserve funds and sovereign wealth funds, and comparatively weak private long-term savings institutions. The current asset allocation to infrastructure by domestic investors is overall very low, and the attractiveness for foreign investors still sub-par. Expectations on the future involvement of investors in this field should be realistic, and there are barriers and risks that need to be worked on. Asian governments can take steps to attract more private capital.
Keywords: G23; G28; G31; H54; O16; O18; 330; infrastructure investment; project finance; public-pricate partnerships